Vaccines for Gonorrhea: Can We Rise to the Challenge? - Zhu, Weiyan; Chen, Ching-ju; Thomas, Christopher E.; Anderson, James E.; Sparling, P. F.; Jerse, Ann E. (Frontiers in Microbiology, 2011)
Immune responses to the gonococcus after natural infection ordinarily result in little immunity to reinfection, due to antigenic variation of the gonococcus, and redirection or suppression of immune responses. Brinton and colleagues demonstrated that parenteral immunization of male human volunteers with a purified pilus vaccine gave partial protection against infection by the homologous strain. However, the vaccine failed in a clinical trial. Recent vaccine development efforts have focused on the female mouse model of genital gonococcal infection. Here we discuss the state of the field, including our unpublished data regarding efficacy in the mouse model of either viral replicon particle (VRP) vaccines, or outer membrane vesicle (OMV) vaccines. The OMV vaccines failed, despite excellent serum and mucosal antibody responses. Protection after a regimen consisting of a PorB-VRP prime plus recombinant PorB boost was correlated with apparent Th1, but not with antibody, responses. Protection probably was due to powerful adjuvant effects of the VRP vector. New tools including novel transgenic mice expressing human genes required for gonococcal infection should enable future research. Surrogates for immunity are needed. Increasing antimicrobial resistance trends among gonococci makes development of a vaccine more urgent.